Odontopus abdominalis (Coleoptera: Curculionidae): a new avocado pest in northeastern Brazil. (2019)
This is the first report of Odontopus abdominalis as a novel pest in avocado orchards in the Alagoas State, in Northeastern Brazil. Adults feed and bore holes in the leaves, and larvae feed on the mesophyll tissue, boring galleries in the leaves. Leaf necrosis then reduces the photosynthetic tissue in the mesophyll. This study contributes relevant information for reporting O. abdominalis as a novel avocado pest in Brazil. This knowledge is essential for defining adequate pest management approaches.